Comparative Analysis of Headspace Volatiles of Different Herbaceous Peony (Paeonia lactiflora Pall.) Cultivars. Issue 1 (2nd January 2016) - Feng, Liguo; Li, Yuemei; Sheng, Lixia; Li, Tinglin; Zhao, Daqiu; Tao, Jun
Abstract: Flower fragrance not only plays an important role for reproduction of ornamental plants, but also improves the aesthetic value of cut flowers and potted plants, the quality of flower products and their economic value. In this study, the floral headspace compounds of different herbaceous peony cultivars were isolated by a headspace solid-phase microextraction, and followed by gas chromatography-mass spectrometry for identification and quantification. Up to 34 volatile compounds were identified from the 21 herbaceous peony cultivars, including 14 terpenes, 9 alcohols, 7 esters, 1 aldehydes, 1 ketones and 2 arenes. Terpenes, alcohols and esters were the major headspace compounds, whereas the main floral constituents identified in herbaceous peony were caryophyllene, β-citronellol and cinnamic acid methyl ester. Paeonia lactiflora 'Zi Rong Xi Yao', Paeonia lactiflora 'Mo Zi Han Jin', Paeonia lactiflora 'Zi Yu Lian' and Paeonia lactiflora 'Xi Xia Ying Xue' had a high total amount of β-citronellol, geraniol, phenylethyl alcohol, nerol and their acetate esters, which were also the major headspace compounds of rose ( Rosa rugosa Thunb.), so they could be considered good materials for improving herbaceous peony fragrance and breeding new cultivars with rose-like fragrance.